HIV Testing in Non-Traditional Settings – The HINTS Study: A Multi-Centre Observational Study of Feasibility and Acceptability - Rayment, Michael; Thornton, Alicia; Mandalia, Sundhiya; Elam, Gillian; Atkins, Mark; Jones, Rachael; Nardone, Anthony; Roberts, Patrick; Tenant-Flowers, Melinda; Anderson, Jane; Ann K. Sullivan on behalf of the HINTS Study Group (PLOS ONE, 2012)
Background UK guidelines recommend routine HIV testing in healthcare settings if the local diagnosed HIV prevalence >2/1000 persons. This prospective study assessed the feasibility and acceptability, to patients and staff, of routinely offering HIV tests in four settings: Emergency Department, Acute Care Unit, Dermatology Outpatients and Primary Care. Modelling suggested the estimated prevalence of undiagnosed HIV infection in attendees would exceed 1/1000 persons. The prevalence identified prospectively was not a primary outcome. Methods Permanent staff completed questionnaires assessing attitudes towards routine HIV testing in their workplace before testing began. Subsequently, over a three-month period, patients aged 16–65 were offered an HIV test by study staff. Demographics, uptake, results, and departmental activity were collected. Subsets of patients completed questionnaires. Analyses were conducted to identify factors associated with test uptake. Findings Questionnaires were received from 144 staff. 96% supported the expansion of HIV testing, but only 54% stated that they would feel comfortable delivering testing themselves, with 72% identifying a need for training. Of 6194 patients offered a test, 4105 (66·8%) accepted (61·8–75·4% across sites). Eight individuals were diagnosed with HIV (0–10/1000 across sites) and all transferred to care. Younger people, and males, were more likely to accept an HIV test. No significant associations were found between uptake and ethnicity, or clinical site. Questionnaires were returned from 1003 patients. The offer of an HIV test was acceptable to 92%. Of respondents, individuals who had never tested for HIV before were more likely to accept a test, but no association was found between test uptake and sexual orientation. Conclusions HIV testing in these settings is acceptable, and operationally feasible. The strategy successfully identified, and transferred to care, HIV-positive individuals. However, if HIV testing is to be included as a routine part of patients’ care, additional staff training and infrastructural resources will be required.